Adsorption and Chromatographic Separation of Mo(VI) and Zr(IV) Ions from a High-Concentration Oxalic Acid Solution by a Macroporous Silica-Based -Tetraoctyl-3-Oxapentane-1,5-Diamide Polymeric Adsorbent - Anyun Zhang; Yuezhou Wei; Harutaka Hoshi; Mikio Kumagai (Adsorption Science & Technology, 2004)
To separate Mo(VI) and Zr(IV) ions from a 0.5 M oxalic acid solution and from each other, a novel macroporous silica-based N,N,N′,N′- tetraoctyl-3-oxapentane-1,5-diamide (TODGA) chelating polymeric adsorbent (TODGA/SiO 2 -P) was synthesized by introducing the TODGA molecule into ca. 50-μm diameter SiO 2 -P particles by impregnation. The adsorption of Mo(VI) and Zr(IV) ions onto TODGA/SiO 2 -P was investigated by examining the influence of nitric acid and oxalic acid concentrations. It was found that the adsorption was strongly affected by increasing the HNO 3 concentration from 0.5 M to 9.0 M either with or without the addition of 0.5 M H 2 C 2 O 4 . In the absence of 0.5 M H 2 C 2 O 4 , the distribution coefficients (K d ) of both Mo(VI) and Zr(IV) ions decreased with an increase in the HNO 3 concentration from 0.5 M to 3.0 M, increased slowly when the concentration of HNO 3 was increased further from 3.0 M to 6.0 M, and then increased gradually above 6.0 M concentration. Furthermore, the adsorption of Zn(IV) ions onto TODGA/SiO 2 -P was considerably greater than that of Mo(VI) ions. In the presence of 0.5 M H 2 C 2 O 4 , Zr(IV) ions showed no adsorption at HNO 3 concentrations below 4.0 M, being partly adsorbed in the presence of 4.0–6.0 M HNO 3 and fully adsorbed when the HNO 3 concentration was greater than 6.0 M. In contrast, Mo(VI) ions showed a much lower adsorption at HNO 3 concentrations below 2.0 M and no adsorption above this acid level. In the presence of HNO 3 at a concentration above 6.0 M and containing 0.5 M H 2 C 2 O 4 , the adsorption of Zr(IV) ions overlapped that from a similar HNO 3 solution which did not include 0.5 M H 2 C 2 O 4 . This was attributed to complete protonation of the C 2 O 2− 2 anion. On the basis of batch experiments, Mo(VI) and Zr(IV) ions were separated from a 6.5 M HNO 3 solution containing 0.5 M H 2 C 2 O 4 by means of a column packed with TODGA/SiO 2 -P at 50°C. The separate components, Mo(VI) and Zr(IV), could be effectively separated from each other by eluting with some selected eluants. The recovery percentage was 100.5% for Mo(VI) ions and 96.8% for Zr(IV) ions.